Myth and philosophy: The Great Sinner’s topos in Ovid, Lucretius and Seneca - Martorana, Simona (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In my paper I examine the occurrence of a repeated pattern, namely the catalogue of the so-called Great Sinners, in the work of three Latin authors: Ovid, Lucretius and Seneca. Through the hermeneutical category of (external) intertextuality, the paper explores how the same Leitmotiv is profitably employed by different authors across diverse genres and contexts, changing certain features while retaining the same core. Specifically, it will be shown that these Latin writers drew the list of the Great Sinners from previous sources, but that they also adapted the catalogue to the content and patterns of their own works. Finally, it is noted that these three occurrences of the catalogue should be seen more generally as a specimen for the process of imitatio/aemulatio of previous traditions brought forth by classical writers.